Favipiravir, will it be the Answer for the Specific Management of COVID-19?: A Review (Medico Legal Update, 2021)
Background: The COVID-19 has created havoc all over the world as no specific treatment available tilldate. Total COVID-19 cases had crossed 11,125,245 including 528,204 deaths as per the WHO data till 5July 2020. Unfortunately, India secured third place in total tally of COVID-19 cases with 6,77,719 totalcases including 19693 deaths as of 5th July 2020. The antiviral drug, Favipiravir, previously known as T-705approved in Japan for treatment of Influenza. It is selective & potent inhibitor of viral RNA polymerase. Itis promising drug for treatment of wide range of RNA viruses including SARSCoV-2.Method: The systematic review of Articles was done with the help of search engines like Embase, Medline,PubMed & Google Scholar, clinicaltrials.gov. The Peer reviewed articles published through 6th of July 2020were included in the study. This review was done to establish clinical evidence for use of Favipiravir inCOVID-19.Conclusion: It was found that due to lack of conclusive evidence, Favipiravir cannot be included in mainarmamentarium for COVID-19.